2008
DOI: 10.1016/j.jasms.2007.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of H2 from CH3CH=N+HCH3: A synchronous, concerted 1,4-H2 elimination

Abstract: Most H 2 eliminations from cations in the gas phase are formally 1,1-or 1,2-processes. Larger ring size H 2 eliminations are rare and little studied. Thus, whether the 6-center, 1,4-elimination CH 3 CHϭN ϩ HCH 3 ¡ CH 2 ϭCHN ϩ HϭCH 2 ϩ H 2 is concerted and synchronous, as indicated by isotope effects and predicted by conservation of orbital symmetry, is a significant question. This reaction is characterized here by application of QCI and B3LYP theories. CH bond-breaking and H-H bond-making in this reaction are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, whereas we attribute this to the avoidance of orbital symmetry constraints, Dewar concluded that multiple bonds do not break simultaneously because that would require an amount of energy roughly equal to the sum of the energies required to break each bonds individually [1]. Given that we recently found that H 2 elimination from CH 3 CHϭNH ϩ CH 3 , an orbital symmetry allowed 1,4-process with a high reverse critical energy, is highly synchronous [45], we believe that orbital symmetry restraints significantly influence the mechanisms of 1,2-eliminations by preventing synchronized trajectories from being taken. This is not necessarily incompatible with the ideas of Dewar.…”
Section: Discussionmentioning
confidence: 83%
“…However, whereas we attribute this to the avoidance of orbital symmetry constraints, Dewar concluded that multiple bonds do not break simultaneously because that would require an amount of energy roughly equal to the sum of the energies required to break each bonds individually [1]. Given that we recently found that H 2 elimination from CH 3 CHϭNH ϩ CH 3 , an orbital symmetry allowed 1,4-process with a high reverse critical energy, is highly synchronous [45], we believe that orbital symmetry restraints significantly influence the mechanisms of 1,2-eliminations by preventing synchronized trajectories from being taken. This is not necessarily incompatible with the ideas of Dewar.…”
Section: Discussionmentioning
confidence: 83%